Atomistic phase field chemomechanical modeling of dislocation-solute-precipitate interaction in Ni–Al–Co. (15th August 2019) - Mianroodi, Jaber Rezaei; Shanthraj, Pratheek; Kontis, Paraskevas; Cormier, Jonathan; Gault, Baptiste; Svendsen, Bob; Raabe, Dierk
Abstract: Dislocation-precipitate interaction and solute segregation play important roles in controlling the mechanical behavior of Ni-based superalloys at high temperature. In particular, the increased mobility of solutes at high temperature leads to increased dislocation-solute interaction. For example, atom probe tomography (APT) results [1 ] for single crystal MC2 superalloy indicate significant segregation of solute elements such as Co and Cr to dislocations and stacking faults in γ′ precipitates. To gain further insight into solute segregation, dislocation-solute interaction, and its effect on the mechanical behavior in such Ni-superalloys, finite-deformation phase field chemomechanics [2 ] is applied in this work to develop a model for dislocation-solute-precipitate interaction in the two-phase γ - γ′ Ni-based superalloy model system Ni–Al–Co. Identification and quantification of this model is based in particular on the corresponding Ni–Al–Co embedded atom method (EAM) potential [3 ]. Simulation results imply both Cottrell- and Suzuki-type segregation of Co in γ and γ' . Significant segregation of Co to dislocation cores and faults in γ′ is also predicted, in agreement with APT results. Predicted as well is the drag of Co by γ dislocations entering and shearing γ' . Since solute elements such as Co generally prefer the γ phase, Co depletion in γ′ could be reversed by such dislocation drag. The resulting change in precipitate chemistry may in turn affect its stability and play a role in precipitate coarsening and rafting. Graphical abstract: Image 1